Comparison of Health-Related Quality of Life in Patients With Various Types of Multiple Sclerosis - Vahid Maroof (Physical Treatments, 2017)
Purpose: Chronic diseases affect patients’ Quality of Life (QoL) and even their caregivers. By evaluating the QoL of patients with multiple sclerosis, the undiagnosed problems of the patients can be detected and the appropriate treatment objectives can be determined. This study was conducted to evaluate the QoL in patients with different types of MS. Methods: A total of 314 patients with Multiple Sclerosis (MS) referred to “Society for the support of MS patients”, “Raad Charity and Education complex”, and an outpatient clinic in Tehran during fall and winter 2014-2015 were recruited. All patients completed the 36-Item Short Form questionnaire (SF-36) and Dartmouth Coop Functional Health Assessment/World Organization of National Colleges, Academies and Academic Association of General Practitioners (COOP/WONCA) functional health assessment charts as self-report. Results: To investigate the research hypothesis and analyzing the results of the two questionnaires, 1-way analysis of variance (ANOVA) was used. The results of the analysis showed a significant difference between the three types of MS (relapsing-remitting, secondary progressive and primary progressive) in the scores of all SF-36 questionnaire subscales. A significant difference was also found between the three types of MS regarding the scores of all charts of COOP/WONCA, except for social support. Then with the use of LSD post hoc test, scores of both questionnaires subscales in these three types of MS were pair-wisely compared. Conclusion: The results showed that the type of MS disease can affect the patients’ QoL. Patients with relapsing-remitting MS had the best level of QoL among all others. The COOP/WONCA charts were more sensitive in measuring the differences between the secondary-progressive MS and primary-progressive MS.